2022
DOI: 10.2215/cjn.01850222
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-Care Ultrasound Training during Nephrology Fellowship

Abstract: Background and objectivesPoint-of-care ultrasound (POCUS)—performed by a clinician during a patient encounter and used in patient assessment and care planning—has many potential applications in nephrology. Yet, US nephrologists have been slow to adopt POCUS, which may affect the training of nephrology fellows. This study sought to identify the current state of POCUS training and implementation in nephrology fellowships.Design, setting, participants, & measurementsConcise survey instruments measuring attitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
(24 reference statements)
0
9
0
Order By: Relevance
“…Recently, a national survey of nephrology fellows and training program directors demonstrated that point-of-care ultrasound (POCUS) is starting to fill that role with 38% of nephrology trainees reporting some form of POCUS education [36 ▪▪ ]. More investment is needed on the part of fellowships with only one third of those fellows reporting POCUS training feeling confident in performing POCUS [37 ▪ ].…”
Section: Training In Clinician-performed Ultrasound: An Unmet Needmentioning
confidence: 99%
“…Recently, a national survey of nephrology fellows and training program directors demonstrated that point-of-care ultrasound (POCUS) is starting to fill that role with 38% of nephrology trainees reporting some form of POCUS education [36 ▪▪ ]. More investment is needed on the part of fellowships with only one third of those fellows reporting POCUS training feeling confident in performing POCUS [37 ▪ ].…”
Section: Training In Clinician-performed Ultrasound: An Unmet Needmentioning
confidence: 99%
“…We have previously outlined the scope and value of multi-organ POCUS in nephrology and provided a detailed blueprint of our curriculum [2,3]. However, despite growing interest among nephrologists, structured POCUS education remains rudimentary in most of the nephrology fellowship programs, which was recently highlighted by Moore et al [4] in their national survey. Not unsurprisingly, the most frequently reported barrier to POCUS program development was the lack of trained faculty.…”
Section: Introductionmentioning
confidence: 99%
“…Moore et al . (2) surveyed fellows and training program directors/associate program directors (TPDs/APDs) using a digital survey instrument. Demographic information was broadly representative of fellows as a whole.…”
mentioning
confidence: 99%
“…Indeed, discussion is ongoing about whether to add core POCUS competencies to the Accreditation Council for Graduate Medical Education (ACGME) requirements for nephrology training programs. In this issue of CJASN, Moore et al (2) present data from a national survey of nephrology fellows and training program directors on training in POCUS. They demonstrate the existence of established POCUS education in a substantial portion of nephrology training programs and the desire on the part of the vast majority of fellows and training program directors to expand learning opportunities in this sector.…”
mentioning
confidence: 99%
See 1 more Smart Citation